Strategi Pencegahan Gizi Kurang pada Bayi melalui Pelatihan Pembuatan Makanan Pendamping ASI (MP-ASI) Berbasis Kearifan Lokal di Desa Tanakaraeng - Ani Tri Prianti; Imran Pashar; Andi Fatwa Tenri Awa (Universitas Muhammadiyah Semarang, 2022)
MP-ASI is a process of transition from purely milk-based intake to semi-solid foods. The introduction and administration of MP-ASI should be carried out in stages, both in form and in quantity, according to the baby's/child's digestive ability (1). the existence of a cadre group is a community institution that assists the Manuju Puskesmas Tanakaraeng Village program in the health sector, especially Maternal and Child Health (MCH) services which will then play a role in assisting in improving the nutritional status of infants and toddlers as well as efforts to reduce stunting in the community in Tanakaraeng Village. As for the activities carried out in the Gowa district, namely the Tanakaraeng Village community, that seeing the conditions in the Tanakaraeng community there are still many infants and toddlers experiencing stunting with an indicator of infant status as many as 67 the number of infants and toddlers (44.79%) who experience malnutrition status is still quite large . The aim of the activity is to increase the ability of participants to be able to process food ingredients made from herbal complementary foods in the surrounding community. The method used in this activity is a method that focuses on the activeness of participants and demonstrations. The training method goes through 3 stages, namely the first stage, planning training activities for making MP-ASI made from herbs, Second, conducting cadre training with Unimerz Nutrition Study Program lecturers, and Third, evaluating the ability of cadres to process herbal complementary foods made from ASI. Fourth, making MP-ASI for the Tanakarang village community. Fifth, the results of the training participants' activities were able to utilize and manage plants made from herbs as complementary foods, including Moringa leaves, sweet potato leaves, etc. high nutritional value without the need to spend money, and an increase in public knowledge in making MP-ASI seen from the evaluation results where the community already knows how to process MP-ASI food ingredients so that the nutritional value is not lost so that the child's nutritional adequacy rate is met and can prevent stunting.